Crecimiento, condición y mortalidad del charal Chirostoma humboldtianum (Atheriniformes: Atherinidae) en México - Aguilar P., J. F. (1996)
The silverside fish (Chirostoma humboldtianum) was studied at the San Felipe Tiacaque dam. Mexico state. México. Sampling was done once during each season of 1987, in three sampling stations al the shore with a 30 m long nel (1.5 I "hanging'·. 0.8 cm aperture).. Four age groups were determined (scale method). The growth rates were: spring -0.1778. summer -0.3364. fall =-0.2032 and winter -0.2869. Corresponding condition factors were 0.0170, 0.0101. 0.071 and 0.032. respectively. Mortalities were -2.5649. -1.2489, -1.1513 and -2.5649 . respectively. Spring is the time of the highest condition factor and food abundance (the silverside is planktivorous) but also of lowest growth because resources are allocated 10 reproduction. Growth is concentrated in the summer. Al values are low in autumn when food is scarce and reach low peaks in winter, when nevertheless the fish is able 10 grow in length (but not in weight).